Claudius, Elephants and Britain: Making Sense of Cassius Dio 60.21.2. (November 2022) - Charles, Michael B.; Singleton, Michael
Abstract: Narratives of the Claudian invasion of Britain in a.d. 43 have regularly referred to elephants being part of Claudius' force, with some accounts even suggesting that Claudius paraded the beasts through Colchester (Camulodunum), or even rode on top of one. This study investigates these claims, which derive solely from a somewhat ambiguous reference in Cassius Dio's (60.21.2) description of the invasion. Temporal and logistical constraints, together with military and iconographic considerations, however, make it highly unlikely that the animals, even if they had been assembled on the Channel, made their way across to Britain. Overall, the study shows that Dio's testimony should be treated with extreme caution, and should be accorded only parenthetical importance in treatments of the Claudian invasion.